Alternative sites for recreation area in Larut Matang Mangrove Forest Reserve, Taiping, Perak - Ayob, Noorhidayah (2016)
Larut Matang Mangrove Forest (LMMF) in Taiping, Perak offers the environment for ecotourism recreational activities in mangrove area to the visitors. Recreation site and study site have a relationship between substitutes and complements. Recreation site usually has substitutes. In this research, the aims are to determine the ecotourism economic value of LMMF using travel cost method (TCM), and more specifically, to determine the alternative recreation site, factors affecting the alternative recreation site and the socio-demographic background of visitors of LMMF. One of the common issues in travel cost studies is to obtain the travel cost from any specific destination to the alternative recreation site. Structured questionnaire and on-site data collection methods are employed to obtain the primary data from the respondents. The count data with a sample size of 300 was modeled with a linear regression model. Based on this study, five variables were tested mainly age, income, distance to alternative sites, travel cost to alternative sites and attractiveness. The variables that showed significant value which affected the demand for LMMF at Taiping Perak were travel cost to alternative sites and attractiveness. An estimate of consumer surplus (CS) per person per visit, as well as the total recreational value for year 2015, was computed. The value estimated was RM RM2,037.50 per visit per person and the total approximation recreational value of LMMF for year 2015 was RM97,679,787.50. This data is for the use of stakeholder especially Perak State Forestry Department in order to foresee valuable natural resources that might have the potential to improve the economy of local community in LMMF.